Main viruses in sweet cherry plantations of Central-Western Spain (Scientia Agricola, 2015)
Sweet cherry trees (Prunus avium L.) are susceptible to a range of diseases, but there have been no studies to date about the viral infection of sweet cherry trees in Spain. To determine the phytosanitary status of Spanish sweet cherry plantations, the incidence and leaf symptoms induced by Prune dwarf (PDV), Prunus necrotic ringspot (PNRSV) and Apple chlorotic leaf spot (ACLSV) viruses were investigated during 2009. Young leaf samples were taken from 350 sweet cherry trees, corresponding to 17 cultivars, and were analysed by double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA). To associate the leaf symptoms with the virus, 50 mature leaves from each infected tree were visually inspected during the summer. The ELISA results revealed that 72 % of sweet cherry trees were infected by at least one of the viruses. PDV occurred in all sampled cultivars and presented the highest infection rate, followed by ACLSV and PNRSV. A high number of trees showed asymptomatic, in both single and mixed infections. The leaf symptoms associated with the viruses involved generalized chlorosis around the midvein (PDV), chlorotic and dark brown necrotic ringspots on both secondary veins and intervein regions (PNRSV), chlorotic and reddish necrotic ringspots (ACLSV) and generalized interveinal chlorosis (PDV-PNRSV).